Cluster Headache. Issue 1 (1st October 2001) - Matharu, Manjit; Goadsby, Peter
Abstract : Cluster headache (CH) is a strictly unilateral headache that occurs in association with cranial autonomic features and, in most patients, has a striking circannual and circadian periodicity. It is an excruciating syndrome and is probably one of the most painful conditions known to mankind, with female patients describing each attack as being worse than childbirth. The understanding of cluster headache, in pathophysiological terms, and the management strategies, have altered dramatically in recent years. Interested readers are referred to monographs for greater details (Kudrow 1980; Sjaastad 1992; Olesen et al . 1999). PATHOPHYSIOLOGY Any pathophysiological construct for cluster headache must account for the three major features of the syndrome: trigeminal distribution pain; ipsilateral cranial autonomic features; and the striking tendency to circadian and circannual periodicity. Firstly, the pain-producing innervation of the cranium projects through branches of the trigeminal and upper cervical nerves to the trigeminocervical complex from whence nociceptive pathways project to